Percentage of Coral Reef Lifeforms Using Sentinel-2A at the Gili Air Dive Site - A'zom, As'ad Humam; Hilayana, Sitti; Wahyudi, Rhojim (Jurnal Biologi Tropis, 2025)
Indonesia possesses approximately 51,000 km² of coral reef ecosystems, yet their condition continues to decline due to both human activities and natural factors. One affected area is the Gili Matra Marine Tourism Park (TWP), particularly the Gili Air dive sites, where significant coral reef degradation has been observed. This study aims to determine the percentage of coral lifeforms and assess the accuracy of Sentinel-2A satellite imagery in mapping coral reefs in the area. Field data were collected using the Underwater Photo Transect (UPT) method and analyzed with CPCe software. Sentinel-2A imagery was processed through sunglint correction water column correction and unsupervised classification using ENVI 5.3 and ArcGIS 10.8. The results show coral reef conditions in Gili Air range from moderate to poor, with the highest live coral cover at Air Slove and the lowest at Hans Reef. A total of eleven coral lifeform types were identified. Image classification produced four benthic habitat classes with an overall accuracy of 60.5% and a Kappa index of 18.3%, meeting the minimum standard set by the Indonesian National Standard The study demonstrates that integrating UPT data and Sentinel-2A imagery is effective for mapping coral reefs, although higher-resolution imagery is recommended for better substrate differentiation.